2015
DOI: 10.1128/aem.03404-14
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Treatment for the Control of Reverse Osmosis Membrane Biofouling

Abstract: f Biofouling remains a key challenge for membrane-based water treatment systems. This study investigated the dispersal potential of the nitric oxide (NO) donor compound, PROLI NONOate, on single-and mixed-species biofilms formed by bacteria isolated from industrial membrane bioreactor and reverse osmosis (RO) membranes. The potential of PROLI NONOate to control RO membrane biofouling was also examined. Confocal microscopy revealed that PROLI NONOate exposure induced biofilm dispersal in all but two of the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…The question of reproducibility will also apply to more complex models of biofilm community interactions, which while more challenging, are arguably still tractable. For example, we have shown that an enrichment culture of a mixed microbial community can be used in repeated studies to foul water purification membranes, where the biofouling process and community composition are reproducible within certain limits (Barnes et al ., 2015). Similarly, a highly species rich community undergoing granulation shows a strongly reproducible shift in community composition, driven by quorum sensing, highlighting that high complexity is not a barrier to reproducibility (Tan et al ., 2015).…”
mentioning
confidence: 99%
“…The question of reproducibility will also apply to more complex models of biofilm community interactions, which while more challenging, are arguably still tractable. For example, we have shown that an enrichment culture of a mixed microbial community can be used in repeated studies to foul water purification membranes, where the biofouling process and community composition are reproducible within certain limits (Barnes et al ., 2015). Similarly, a highly species rich community undergoing granulation shows a strongly reproducible shift in community composition, driven by quorum sensing, highlighting that high complexity is not a barrier to reproducibility (Tan et al ., 2015).…”
mentioning
confidence: 99%
“…); this suggests that NO may be useful for treating biofilms in a variety of medical and industrial applications (Barnes et al . ). NO also forms part of a stress‐surveillance system in diatoms (Vardi et al .…”
Section: Challenge 2: Marine Biofilmsmentioning
confidence: 97%
“…Furthermore, because unrestricted use of antibiotics often results in acquired antibiotic resistance that can be dangerous to human health, the development of nature-inspired strategies, including companion cropping, can potentially overcome current limitations in the control of pathogens. Scientists have only now begun to elucidate the molecular mechanisms controlling bacterial biofilm dispersal (Kaplan 2010), but the targeted delivery of the biogenic infochemical nitric oxide (NO) to such biofilms has been shown to stimulate the dispersal of bacteria from an existing biofilm matrix (Barraud et al 2015); this suggests that NO may be useful for treating biofilms in a variety of medical and industrial applications (Barnes et al 2015). NO also forms part of a stresssurveillance system in diatoms (Vardi et al 2006), and recent results suggest that signaling interference might also be a strategy to control diatom biofilm formation.…”
Section: Challenge 2: Marine Biofilmsmentioning
confidence: 99%
“…Bacterial existence in the wild is predominated by life in spatially structured groups, termed biofilms (1,2), which inhabit environments ranging from the rhizosphere (3), to chronic infections (4,5), to the pipes of industrial and wastewater flow systems (6,7), to the surfaces of marine snow (8)(9)(10)(11)(12)(13). Although living in groups correlates with 45 increased tolerance to many exogenous threats, including antibiotic exposure (14-16), biofilm-dwelling cells also experience intense competition for space and resources (2, 17,18).…”
Section: Introductionmentioning
confidence: 99%